Customer Cooperation and Employee Innovation Behavior: The Roles of Creative Role Identity and Innovation Climates - Zhou, Jian; Yang, Jian; Zhou, Xue (Frontiers in Psychology, 2021)
Employee innovation behaviors lay the foundation for sharing economies and are of importance to business success, especially for service sector firms such as hotels. This study examines the relationship between customer cooperation and employee innovation behavior (EIB) by focusing on the mediating role of creative role identity and the moderating role of innovation climate. Drawing on resource based theory and role identity theory, we propose that customer cooperation enhances creative role identities and EIB, and the relationship between creative role identities and EIB is stronger when innovation climates are described as ‘high’ rather than ‘low’. A total of 213 respondents in high star hotel were selected for questionnaire survey in this study. The results indicate that Customer cooperation is positively related to EIB. Customer cooperation positively affects EIB partially through creative role identities and innovation climate strengthens the direct effect of creative role identities on EIB and the indirect effect of customer cooperation on EIB through creative role identities. Theoretical and practical implications were also discussed.